Coming home at last: dermal white adipose tissue. Issue 9 (September 2014) - Schneider, Marlon R.
Abstract The upper part of subcutaneous white adipose tissue (SWAT) is closely associated with the reticular dermis, surrounds hair follicles and is of great importance for a range of skin functions. In this issue of Experimental Dermatology, Driskell and colleagues propose a nomenclature in which the upper SWAT layer is renamed dermal WAT (DWAT), and its cells intradermal adipocytes. Some pros and cons are discussed below.